2003
DOI: 10.1185/030079903125002603
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, randomised, placebo-controlled study to evaluate the efficacy and safety of a fixed combination containing two plant extracts (Crataegus oxyacantha and Eschscholtzia californica) and magnesium in mild-to-moderate anxiety disorders

Abstract: The preparation containing fixed quantities of Crataegus oxyacantha, Eschscholtzia californica, and magnesium proved safe and more effective than placebo in treating mild-to-moderate anxiety disorders. Sympathyl is produced and marketed by Laboratoire Innotech International, Arcueil, France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 8 publications
0
49
0
1
Order By: Relevance
“…A large randomized controlled trial (RCT) found that a combination of Crataegus oxyacantha (hawthorn), Eschscholzia californica (Californian poppy) and magnesium was more effective than placebo in reducing anxiety in 264 individuals with generalised anxiety disorder (Hanus et al, 2004). Another study evaluated for the central effects of the phytotherapeutic product-CPV (dry extract of Crataegus oxyacantha, Passiflora incarnata and Valeriana officinalis) in animals models.…”
Section: Crataegus In Anxiety and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large randomized controlled trial (RCT) found that a combination of Crataegus oxyacantha (hawthorn), Eschscholzia californica (Californian poppy) and magnesium was more effective than placebo in reducing anxiety in 264 individuals with generalised anxiety disorder (Hanus et al, 2004). Another study evaluated for the central effects of the phytotherapeutic product-CPV (dry extract of Crataegus oxyacantha, Passiflora incarnata and Valeriana officinalis) in animals models.…”
Section: Crataegus In Anxiety and Depressionmentioning
confidence: 99%
“…Crataegus showed high antioxidant and immunostimulating activity (Li et al, 2009). Crataegus is also employed in CNS disorders like anxiety and mild depression (Hanus et al, 2004).…”
Section: Congestive Heart Failurementioning
confidence: 99%
“…Parmi les alcaloïdes, la californine est métabolisée de manière extensive par N-déméthylation et par simple ou double déméthylènisation, suivie de catéchol-O-méthylation. La protopine subit uniquement Eschscholzxanthine, anhydro-eschscholzxanthine, 5-retro-β, β-carotene-3,5,3'-triol [8,14] …”
Section: Absorption Métabolisme Et Excrétionunclassified
“…4,5 It is also used in some other critical disease such as control of central nervous system (CNS), anxiety and depression. 6 A Homeopathic medicine has also been prepared from its flowers and fruits by Homeopathic pharmacopeia of India. 7 As food for heart has described.…”
Section: Introductionmentioning
confidence: 99%